Implementasi Pembelajaran Bahasa Arab Dengan Pemanfaatan Teknologi - Rahmalia, Fadlila (Kaisa: Jurnal Pendidikan dan Pembelajaran, 2023)
This article examines how technology can be utilized in the process of Arabiclearning. Many problems of learning of Arabic language in accordance with the context faced in various educational institutions, a teacher allows modification formethodsof teaching and learning. This can be done with technological developments that contain lots of information that can be used to improve learning  outcomes. Discussion about the application of technology in learning Arabic contains the question of what kind of technology that can be utilized, whether the technology can play a role in the alignment and sustainability of learning Arabic from basic to middle level, whether the technology can make learners will be more interested in learning the Arabiclanguage, whether the technology can create realization and relevance to what the students perceived, whether the technology can create Arabic learning media more varied that still lacks, whether the technology can improve the ability or competence of teachers in teaching Arabic, whether technology is able to take advantage of time allocation for learning Arabic, whether the technology is able to create an Arabic speaking environment. Through qualitative descriptive method, this article summarizes some of the above questions. Artikel ini mengeksplorasi bagaimana teknologi dapat digunakan dalam pembelajaran bahasa Arab. Masalah pembelajaran bahasa Arab yang berbeda tergantung pada konteks di lembaga pendidikan yang berbeda, staf pengajar memungkinkan perubahan dalam metode belajar mengajar. Hal ini dapat dilakukan melalui perkembangan teknologi yang mengandung kekayaan informasi yang dapat digunakan untuk meningkatkan hasil belajar. Pembahasan penerapan teknologi dalam pembelajaran bahasa Arab meliputi pertanyaan seperti: bentuk teknologi apa saja yang dapat digunakan, apakah teknologi dapat berperan dalam keserasian dan keberlangsungan pembelajaran bahasa Arab dari SD hingga SMA, apakah teknologi dapat merangsang minat belajar bahasa siswa. Bahasa Arab, teknologi dapat menciptakan pemahaman dan makna bagi perasaan siswa, teknologi dapat menciptakan lingkungan belajar bahasa Arab yang lebih fleksibel, yang kekurangan waktu yang dihabiskan untuk belajar bahasa Arab, teknologi dapat menciptakan lingkungan bahasa Arab. Artikel ini membahas beberapa masalah di atas melalui deskripsi kualitatif.